2022
DOI: 10.1590/0001-3765202220201133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combining Zingiber officinale and Juglans regia extracts on Propionibacterium acnes, Staphylococcus aureus and Staphylococcus epidermidis: antibiofilm action and low toxicity

Abstract: Objective was evaluated the therapeutic effect of Juglans regia (J) and Zingiber officinale (Z) extracts, alone or associated (Z75% + J25%, Z50% + J50% and Z25% + J75%) applied on planktonic cultures and biofilms of Propionibacterium acnes, Staphylococcus epidermidis and Staphylococcus aureus, as well as analyzing the cytotoxic effects of plant extracts on mouse macrophages (Raw 264-7). Broth microdilution assay was performed (M7-A6 -CLSI). Anti-biofilm activities and cytotoxicity on Raw 264-7 were studied usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Panduratin A and isopanduratin A in fingerroot extract displayed antibacterial activity against C. acnes and their MIC values were found to be 2 and 4 μg cm -3 , respectively [40]. Glycolic extracts of ginger were used for antibacterial evaluation on C. acnes ATCC 6919, and it was shown that the ginger extract (100 %) could inhibit the bacterial growth with an MIC value of 12.5 mg cm -3 [41]. Moreover, panduratin A was highly antimicrobial against both Staphylococci and Enterococci isolates [40].…”
Section: Discussionmentioning
confidence: 99%
“…Panduratin A and isopanduratin A in fingerroot extract displayed antibacterial activity against C. acnes and their MIC values were found to be 2 and 4 μg cm -3 , respectively [40]. Glycolic extracts of ginger were used for antibacterial evaluation on C. acnes ATCC 6919, and it was shown that the ginger extract (100 %) could inhibit the bacterial growth with an MIC value of 12.5 mg cm -3 [41]. Moreover, panduratin A was highly antimicrobial against both Staphylococci and Enterococci isolates [40].…”
Section: Discussionmentioning
confidence: 99%
“…The synergy of different plant extracts was tested before and was effective against different microorganisms [22,23]. The main objective of this study was to evaluate the synergistic antibiofilm action of the produced and phytochemically characterized extracts of C. verum and BGP propolis against multidrug-resistant clinical strains of A. baumannii and P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…Phytotherapy is gaining increasing attention in dentistry [11][12][13], particularly in specialized areas such as endodontics [14,15], or as a coating material [16,17] because of its antimicrobial action and biocompatibility. Its use reflects a broader trend towards exploring botanical solutions for dental applications, capitalizing on their well-established antimicrobial qualities and compatibility with oral health treatments.…”
Section: Introductionmentioning
confidence: 99%